The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1103/physrevd.90.123531
|View full text |Cite
|
Sign up to set email alerts
|

Hollow cores in warm dark matter halos from the Vlasov-Poisson equation

Abstract: We report the results of extended high-resolution numerical integrations of the Vlasov-Poisson equation for the collapse of spherically symmetric WDM halos. For thermal relics with mass m = 1 keV/c 2 , we find collapsed halos with cores of size from 0.1 to 0.6 kpc. The typical core is hollow, with the mass density decreasing towards the core center by almost three orders of magnitude from its maximum near the core radius rc. The core is in equilibrium with the diffused part of the halo but far from virializati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 101 publications
(155 reference statements)
0
6
0
Order By: Relevance
“…x we can also infer that most of the hydrogen in the intergalactic medium is ionised, and the neutral hydrogen is mainly contained in the so called damped Lyman-α absorber systems (DLAs) with HI column densities N HI above 2 × 10 20 atoms cm −2 and secondarily in Lyman limit systems (LLS), at 19 Figure 5. HI column density distribution function, f HI (N HI ), obtained by assigning HI to gas particles employing two different methods: halo based (dotted lines) and particle based (solid lines) described in 3.1 3.2.…”
Section: Hi Column Density Distribution Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…x we can also infer that most of the hydrogen in the intergalactic medium is ionised, and the neutral hydrogen is mainly contained in the so called damped Lyman-α absorber systems (DLAs) with HI column densities N HI above 2 × 10 20 atoms cm −2 and secondarily in Lyman limit systems (LLS), at 19 Figure 5. HI column density distribution function, f HI (N HI ), obtained by assigning HI to gas particles employing two different methods: halo based (dotted lines) and particle based (solid lines) described in 3.1 3.2.…”
Section: Hi Column Density Distribution Functionmentioning
confidence: 99%
“…However, there is also a possible way to alleviate at least some small scales problems, while preserving the success of CDM on large scales, by assuming that the dark matter JCAP07(2015)047 particles have intrinsic thermal velocities (although there are works that disagree, see for example [13,14]). On one hand, the presence of thermal velocities will avoid the cuspy clustering of dark matter particles within gravitational potential wells, allowing the formation of cores [15][16][17][18][19] in the density profile, although most of the works have shown that an unrealistic low value of the WDM mass is needed to match observations. On the other hand, the collapse of dark matter halos can only take place for perturbations larger than the typical free-streaming length of the dark matter particles, thus, the presence of thermal velocities in the dark matter particles will naturally suppress the abundance of low mass subhalos [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The prior on γ was chosen to be positive for consistency with similar studies (e.g., Barnabè et al 2012;Cappellari et al 2013;Adams et al 2014) and because inner DM depression with γ < 0 is a regime not yet explored by numerical simulations, with a few exceptions (e.g., Destri 2014).…”
Section: Maximum Likelihood Analysismentioning
confidence: 99%
“…The prior on the stellar mass-to-light ratio includes the values predicted by stellar population models for NGC 1407 (Zhang et al 2007;Humphrey et al 2006) The prior on γ was chosen to be positive for consistency with similar studies (e.g., Barnabè et al 2012;Cappellari et al 2013;Adams et al 2014) and because inner DM depression with γ < 0 is a regime not yet explored by numerical simulations, with a few exceptions (e.g., Destri 2014).…”
Section: Maximum Likelihood Analysismentioning
confidence: 99%
“…The 'core-cusp' problem may evince DM properties beyond the CDM paradigm. McDonald & Sahu (2009); Angulo et al (2013); Destri (2014); González-Samaniego et al (2016) argue that DM particles would be less prone to forming cusped halos if primordial DM either remained relativistic for longer or decoupled later than canonically predicted. Rocha et al (2013); Peter et al (2013); Robles et al (2017); Sokolenko et al (2018); Harvey et al (2018); Robertson et al (2019); Sameie et al (2018); Fitts et al (2019); Robles et al (2019) claim that self-interacting dark matter (SIDM) could virialize dense DM cusps, turning them into a cores.…”
Section: Introductionmentioning
confidence: 99%